Effect of Addition Fermented Cabbage Extract on Antioxidant Activity and Antinutritional Compounds of Foxtail Millet Flour - Diode Yonata; Boby Pranata; Siti Aminah (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
Fermented cabbage extract contains lactic acid bacteria Lactobacillus plantarum which produces tannase enzymes and Lactobacillus casei which produces phytase enzymes, which are very effective in reducing antinutrient compounds and increasing the antioxidant compound foxtail millet flour. This study aimed to determine the optimal fermentation time (0, 12, 24, 36, and 48 hours) to decrease antinutrient compounds and increase antioxidant compounds of foxtail millet flour using fermented cabbage extract. The results showed that an increase in fermentation time from 0 to 48 hours reduced levels of tannins and phytic acid in foxtail millet flour by 68.64 % (2.71 - 0.85 mg/g) and 66.60 % (5.33 - 1.78 mg/g) respectively. Afterwards there is an increase in antioxidant activity by 83.10 % (42.25 - 77.26 %) and a decrease in total phenolic content by 18.22 % (7.41 - 6, 06 mg GAE/g). In conclusion, the optimal fermentation time to produce FMF with the best characteristics (low antinutrients and high antioxidant activity) is 48 hours. Keywords:   phytic acid, tannin, antioxidant activity, foxtail millet flour, fermented cabbage extract